The Influence of Leadership Style, Motivation and Work Discipline as Intervening Variables on Employee Performance (Case Study at Securities Company) - Ritonga, Suryani; Safaria, Siti (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research is using quantitative approach by saturated sampling on empoyees. total population are 76 employees. The data obtained is using Partial Least Square (PLS). The results are leadership style affected employee work discipline. motivation affected work discipline. Work discipline not affected employee performance. leadership style have not affected employee performance. motivation effected employee performance. Indirectly, work discipline cannot mediate leadership style on employee performance. discipline cannot mediate motivation on employee performance. So that the results obtained are insignificant results